Cardiac Physical Exam Skills and Auscultation Session for Pediatric Interns - Christopher A. Sumski; Anoop Singh; Amanda Rogers; Robert Treat; Charles Bergstrom (Association of American Medical Colleges, 2022)
Introduction Physicians need adequate physical exam skills. Unfortunately, interns have variable physical exam skills, and teaching is often limited to rounds, an inconsistent setting. Physical exam skills, particularly those involving auscultation, require practice. Our goal was to create a cardiac physical exam workshop for pediatric interns that would improve their performance on an interactive assessment of their ability and understanding in physical exam and murmur interpretation. Methods We completed a targeted needs assessment and then developed a 2-hour workshop on the pediatric cardiac physical exam targeted to pediatrics residents. The workshop included didactics, group discussion, and practice interpreting common pediatric murmurs. Pediatrics residents completed the assessment as a pretest and then participated in the workshop. At the end of the workshop, the assessment was administered as a posttest, followed by a reassessment 3 months later. Nonparametric statistical analysis was conducted. Pre- and posttest scores were compared using the Wilcoxon signed rank test. Results Twenty-five residents completed the workshop, including 22 pediatrics residents, one pediatrics/anesthesia combined resident, one pediatric neurology resident, and one resident completing a preliminary year in pediatrics prior to dermatology residency. There was a significant increase in the mean score on the assessment from pre- to posttest (pretest M = 54%, posttest M = 71%, p < .001). This increase was sustained at the 3-month reassessment (M = 67%). Discussion This cardiac physical exam workshop demonstrated improvement in physical exam knowledge and interpretation ability as measured by an online pre-/posttest.